2018
DOI: 10.1063/1.5048304
|View full text |Cite
|
Sign up to set email alerts
|

Particle-scale statistical theory for hydrodynamically induced polar ordering in microswimmer suspensions

Abstract: Previous particle-based computer simulations have revealed a significantly more pronounced tendency of spontaneous global polar ordering in puller (contractile) microswimmer suspensions than in pusher (extensile) suspensions. We here evaluate a microscopic statistical theory to investigate the emergence of such order through a linear instability of the disordered state. For this purpose, input concerning the orientation-dependent pairdistribution function is needed, and we discuss corresponding approaches, par… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 115 publications
1
41
0
Order By: Relevance
“…[12][13][14][15] For front-actuated (puller) swimmers such as Chlamydomonas, no such collective behaviour is observed in 3-dimensional suspensions, 7,16 although instead a transition to a polar flocking state has been observed in simulations of puller stresslets confined to a 2-dimensional plane. 17,18 We also note that, in the case of squirmers, which swim by an imposed slip flow along the spherical [19][20][21] or elongated 22,23 swimmer body, such a polar state is found for pullers also in 3 dimensions, while no sign of collective behaviour is found in the corresponding pusher suspensions. 19,21 While squirmers is a more appropriate model for ciliated organisms such as Paramecium, these different collective behaviours highlight that the aspect ratio and seemingly subtle differences in the near-field flows can have large impacts on the non-equilibrium steady states.…”
Section: Introductionmentioning
confidence: 77%
“…[12][13][14][15] For front-actuated (puller) swimmers such as Chlamydomonas, no such collective behaviour is observed in 3-dimensional suspensions, 7,16 although instead a transition to a polar flocking state has been observed in simulations of puller stresslets confined to a 2-dimensional plane. 17,18 We also note that, in the case of squirmers, which swim by an imposed slip flow along the spherical [19][20][21] or elongated 22,23 swimmer body, such a polar state is found for pullers also in 3 dimensions, while no sign of collective behaviour is found in the corresponding pusher suspensions. 19,21 While squirmers is a more appropriate model for ciliated organisms such as Paramecium, these different collective behaviours highlight that the aspect ratio and seemingly subtle differences in the near-field flows can have large impacts on the non-equilibrium steady states.…”
Section: Introductionmentioning
confidence: 77%
“…where 0 g is the strength of the interaction, and x 1 Q = ( ) for x 0  and zero otherwise. Note that this is a simplified ansatz that describes the polar alignment of neighboring swimmers due to near-field hydrodynamics interactions [72], an effect that has been observed experimentally [3]. Finally, the external potential for swimmer μ is given by Coming back to equations (A.1) and (A.2), far-field hydrodynamic interactions are taken into account by the coupling terms involving the average surrounding flow field u.…”
Section: Discussionmentioning
confidence: 96%
“…In earlier publications [18,19] we have shown that an equivalent hydrodynamic theory for the microswimmer velocity can be derived via a Fokker-Planck equation approach starting from a generic Langevin model (similar to [15,16]) for a system of microswimmers of length ℓ, diameter d and self-swimming speed v 0 with constant density ρ (see appendix A for a summary of the derivation). The Langevin model includes two types of interactions: first, there are short-range contributions stemming from an activity-driven polar interaction characterized by strength γ 0 and range r [72]. Second, far-field hydrodynamic effects are included via a coupling to the solvent flow field u.…”
Section: Hydrodynamic Theorymentioning
confidence: 99%
“…159 Such order in the swimmer orientations naturally leads to collective motion, maintaining a common average propulsion direction. More-over, we have performed a corresponding linear stability analysis of our DDFT for planar pure (one-species) pusher or puller systems, with spontaneous ordering identified beyond a threshold active drive for pullers, 108 in contrast to pushers. We now address the corresponding two-species situation.…”
Section: B Emergence Of Polar Orientational Order and Collective Motmentioning
confidence: 99%
“…(69), were determined in Ref. 108 by a modified Percus test-particle method. For this purpose, hydrodynamic interactions were neglected and only the interplay of self-propulsion and steric interactions was evaluated.…”
Section: B Emergence Of Polar Orientational Order and Collective Motmentioning
confidence: 99%